MENINGKATKAN KETERLIBATAN AKADEMIK SELAMA PEMBELAJARAN DARING MELALUI BIMBINGAN KELOMPOK DENGAN METODE ADVERSITY QUOTIENT - Ahmad Luthfi Ihza Maulana; Sucipto Sucipto; Masturi Masturi (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The objectives of this research are: (1) To describe the application of group guidance with an adversity queent approach in increasing academic engagement during online learning. (2) Describe the increase in academic involvement during online learning after the implementation of group guidance with the adversity quetent approach. Academic involvement is an attitude that must be shown by all students of class XI Islamic Banking at SMK 1 Kudus by being actively involved in the learning process. Group guidance is an activity carried out by a group of people by utilizing group dynamics. Adversity Quotient is a person's ability to use his intelligence to direct, change his way of thinking and actions when facing obstacles and difficulties that can make it difficult for him. This research was conducted at SMK 1 Kudus. The research design uses guidance and counseling action research. Subjects were six students of class XI Islamic Banking. Data collection techniques using observation, and interviews. The data analysis used is descriptive quantitative data analysis. The conclusions of this study are as follows: (1) Implementation of group guidance with the adversity quotient method to increase academic involvement during online learning in class XI Islamic Banking SMK 1 Kudus in the first cycle obtained a score of 49% (less), in the second cycle it increased to 77% (Well). (2) Academic involvement during online learning for students of class XI Islamic Banking at SMK 1 Kudus has increased. This statement can be seen from the research progress, pre-cycle academic engagement scores during online learning are 38% (very poor), cycle I is 53% (poor), and cycle II is 81% (good).